Computed tomography in predicting gall stone solubility: a prospective trial. Issue 5 (May 1992) - Caroli, A; Del Favero, G; Di Mario, F; Spigariol, F; Scalon, P; Meggiato, T; Zambelli, C; Naccarato, R
Abstract : This prospective study was undertaken to evaluate the correlation between densitometric values of gall stones assessed by computed tomography and the success rate of litholytic therapy in 28 patients eligible for oral treatment. A densitometric study of the stones was performed in all patients before treatment. A cut off point of 60 Hounsfield units (HU) was chosen to divide the subjects into two groups–group 1, 14 patients with low density stones (less than 60 HU) and group 2, 14 patients with high density stones (greater than 60 HU). All patients were treated with ursodeoxycholic acid (8-10 mg/kg/day) for 12 months and followed up by ultrasound. In group 1, dissolution was complete in 50% of the patients and partial in a further 20%. In group 2 patients, complete dissolution was not observed but 33% showed partial dissolution. The number of patients with total dissolution at 12 months was significantly higher in group 1 compared with group 2 (p less than 0.02). These results suggest that computed tomography can be used to select patients with a better likelihood of successful stone dissolution after bile acid therapy.